Caracterização do processo de secagem do café natural submetido a diferentes métodos de secagem - Moreira, Rodrigo Victor (2015)
Drying is one of the main factors that influence the quality of natural coffee and, consequently, its commercial value. The development of dryers that quickly dehydrate the fruits, without the use of elevated drying temperatures, has proven to be a promising alternative, especially for ensuring the quality of natural coffees. This quick dehydration can be obtained through the use of drying air with low relative humidity, combined with reduced temperatures. Thus, the aim of the present study was to characterize the drying process and the final quality of the coffee, which was dry-processed and dried under different methods. The Coffea arabica L. fruits were harvested, processed, and dried on a farm in Franca, SP, Brazil, while the beneficiation and analyses were performed at the Universidade Federal de Lavras, in partnership with the Empresa de Pesquisa Agropecuária de Minas Gerais (EPAMIG), both in the municipality of Lavras, MG, Brazil. The fruits, with the same initial moisture content, were dried in three different ways until reaching from 11% to 12% (wet base) water content, namely: complete drying in the sun on a cement drying patio; complete drying in a tray dryer equipped with a boiler and air treatment unit (ATU) which, by means of a compression system, dehumidifies the drying air at levels ranging from 10% to 15% relative humidity; and complete drying in a rotating dryer fed by boiler. We performed three drying tests and, to characterize the process, the drying curves of the mechanical methods were plotted. For quality characterization, we performed the following analyses: sensory, total sugars (TS), total titratable acidity (TTA), potassium leaching (KL), electrical conductivity (EC), and polyphenoloxidase enzyme activity (PPO), as well as color, size, and shape analyses. We concluded that it is possible to obtain a higher drying rate using tray dryers with ATU, compared to rotating dryers or a sun drying patio, without compromising the quality of the product. Even with similar values of drying air temperature, the tray dryer with ATU provides better drying speed compared to rotating dryers. Coffees of higher quality in the properties EC, KL, TTA, TS, and PPO may be obtained through use of tray dryers with ATU. The variables that most discriminate sun-dried coffee from coffee dried in rotating or tray dryers are flavor, balance, and final score. The variables that most discriminate coffee from the tray dryer with ATU and the rotating dryer are drying air temperature and grain weight temperature, EC, KL and TTA. In sensorial analysis, the coffees obtained from the three drying methods were classified as specialty coffees, with scores from 81.61 to 82.17. The drying methods did not differ in regard to the color of the green coffee, however, they may influence the dimensions and shapes of the coffee fruits and coffee beans.